Noun Phrases in Aceh Language Pantun Collections - Kartika, Rika; Mulyadi, Mulyadi (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to describe noun phrases in Acehnese pantun collections. The research method used in this research is descriptive qualitative. Data collection in this research is by browsing the Aceh Language Centre website. Qualitative Data Analysis Technique Miles and Huberman Model Miles and Huberman can be done through three stages, namely data reduction, data display, and conclusion drawing / verification. The data found related to noun phrases in Acehnese pantun are first, when associated with noun + noun contained in the pantun array, there are 16 noun words containing the meaning of nouns in a pantun using Acehnese language. In the noun + verb found as many as 4 words containing the meaning of nouns and verbs. In the noun + adjective, 6 words were found containing the meaning of nouns juxtaposed with adjectives.